Risiko di Bank Syariah: Suatu Pengantar - Cipta, Hendra (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2018)
Islamic banks are banks whose products range from funding to financing. With more and more of these products, of course the risks faced by Islamic banks are also increasingly diverse. So, through this article will explain what risks are faced by conventional banking and Islamic banking. This article will also outline the risks faced by financing channeled by Islamic banks and how to implement risk management in Islamic banks to mitigate the risks they face.